Time Can Flow in the Opposite Direction of What We Think It Does - Morita, Kunihisa (Problemos, 2025)
Attitudes towards the future and the past differ. This difference seems easy to explain if time actually flows, and thus, has an intrinsic direction. At first, this appears to be an advantage of the dynamic view of time, according to which time really flows, over the static view of time, according to which time does not flow. However, this paper aims to demonstrate that the intrinsic direction built into the dynamic view of time can point in the direction opposite of that in which we believe that time progresses, thereby rendering the dynamic view futile for explaining why attitudes towards the past and the future differ. Therefore, this advantage of the dynamic view of time over the static view becomes invalid.